Synthesis, physicochemical characterization and antibacterial activity of novel (benzoylamino)methyl derivatives of quinolones - Breznica-Selmani, Pranvera; Mladenovska, Kristina; Dräger, Gerald; Mikhova, Bozhana; Panovski, Nikola; Kaftandzieva, Ana; Kavrakovski, Zoran; Hoxha, Ahmet; Sheqerxhiu, Nardi; Jurhar Pavlova, Maja; Popovski, Emil (Society of Chemists and Technologists of Macedonia, 2016)
Herein we report the synthesis of different derivatives of (fluoro)quinolones norfloxacin, ciprofloxacin and pipemidic acid, by incorporating (benzoylamino)methyl on the free nitrogen of the pyperazinyl moiety. The compounds were structurally characterized by 1D and 2D NMR, FTIR and high-resolution mass spectroscopy. In addition, their physicochemical properties were a matter of interest to be correlated with their structure and antimicrobial activity in vitro. Their antimicrobial activities were screened against Gram-positive, Gram-negative bacteria and C. albicans. Higher distribution coefficients and consequently lower water solubility were determined for all synthesized compounds than the ones of the corresponding leading compounds. Inconsequential correlations between the lipophilicity of the compounds and MIC were observed, suggesting that passive diffusion is not the only mechanism for their penetration into bacterial cells. Further studies are needed to determine how substitutions in the (fluoro)quinolone moiety affect the primary target(s), substrate behavior in respect to bacterial transporters and overall bioavailability.